European Small Business Finance Outlook 2022 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2022)
This working paper provides an overview of the main markets relevant to the EIF, thereby documenting the impact of the current inflationary environment, the war in Ukraine and the aftermath of the pandemic on the SME financing environment. The publication first discusses the general market environment and then covers the markets for SME equity and debt products. In addition, it focuses on a number of thematic policy areas that are of particular interest to the EIF, such as Inclusive Finance, Fintech and Green finance & investment.
Keywords: 330; SMEs; SME financing; private equity; bank guarantee; microfinance; financial technology; sustainable investment; Europe; KMU; Mittelstandsfinanzierung; Private Equity; Bankgarantie; Mikrofinanzierung; Finanztechnologie; Nachhaltige Kapitalanlage; Europa